2022
DOI: 10.3390/molecules27227948
|View full text |Cite
|
Sign up to set email alerts
|

Iron Porphyrin as a Cytochrome P450 Model for the Degradation of Dye

Abstract: Organic dyes are widely used in the textile, biological, medical and other fields. However, a serious environmental problem has appeared because of the presence of organic dyes in industrial aqueous effluents. Thus, the efficient treatment of organic dyes in industrial wastewaters is currently in real demand. The current study investigated the oxidative degradation of the organic dye gentian violet by meso-tetra(carboxyphenyl) porphyriniron(III), [FeIII(TCPP)] as a cytochrome P450 model and iodosylbenzene (PhI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…In a recent study, Meyer et al reported that an iron porphyrin, meso -tetrakis(1-methylpyridinium-4-yl)prophyrinatoiron(III) ([Fe III (tmpyp)]), was an efficient catalyst to degrade azo dyes with meta -chloroperoxy benzoic acid as an oxidant in an aqueous solution at room temperature [ 49 ]. Very recently, our group investigated a ferric porphyrin complex, Fe(III)TCPP, in combination with an oxidant, PhIO, that exhibited a high catalytic efficiency for the degradation of gentian violet [ 50 ]. However, very limited iron porphyrins were reported to catalyze the oxidative degradation of triphenylmethane dyes.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Meyer et al reported that an iron porphyrin, meso -tetrakis(1-methylpyridinium-4-yl)prophyrinatoiron(III) ([Fe III (tmpyp)]), was an efficient catalyst to degrade azo dyes with meta -chloroperoxy benzoic acid as an oxidant in an aqueous solution at room temperature [ 49 ]. Very recently, our group investigated a ferric porphyrin complex, Fe(III)TCPP, in combination with an oxidant, PhIO, that exhibited a high catalytic efficiency for the degradation of gentian violet [ 50 ]. However, very limited iron porphyrins were reported to catalyze the oxidative degradation of triphenylmethane dyes.…”
Section: Introductionmentioning
confidence: 99%